Backstory 5 : Interviews with Screenwriters of the 1990s. - McGilligan, Patrick (Berkeley : University of California Press, 2009)
Patrick McGilligan continues his celebrated interviews with exceptional screenwriters in Backstory 5, focusing on the 1990s. The thirteen featured writers-Albert Brooks, Jean-Claude Carrière, Nora Ephron, Ronald Harwood, John Hughes, David Koepp, Richard LaGravenese, Barry Levinson, Eric Roth, John Sayles, Tom Stoppard, Barbara Turner, and Rudy Wurlitzer-are not confined to the 1990s, but their engrossing, detailed, and richly personal stories create, in McGilligan's words, "a snapshot of a profession in motion." Emphasizing the craft of writing and the process of collaboration, this ne.
McGilligan_FM; McGilligan_Text; McGilligan_Ch01; McGilligan_Ch02; McGilligan_Ch03; McGilligan_Ch04; McGilligan_Ch05; McGilligan_Ch06; McGilligan_Ch07; McGilligan_Ch08; McGilligan_Ch09; McGilligan_Ch10; McGilligan_Ch11; McGilligan_Ch12; McGilligan_Ch13; McGilligan_Contri; McGilligan_BM; McGilligan_Genral Index; McGilligan_Title Index.
Print version record.
Includes bibliographical references and indexes.
JSTOR
Keywords: Screenwriters -- California -- Los Angeles -- Interviews; Scénaristes -- Californie -- Los Angeles -- Entretiens; DRAMA -- American; PERFORMING ARTS -- Film & Video -- General; Screenwriters; California -- Los Angeles; 1990s.; adaptations; albert brooks; backstory; barbara turner; barry levinson; behind the scenes; biographical; career; collaborative projects; contemporary; david koepp; eric roth; fictional works; jean claude carriere; john hughes; john sayles; movie writers; nonfiction; nora ephron; personal interviews; pop culture; popular movies; popular television; richard lagravenese; ronald harwood; rudy wurlitzer; screenwriters; stage plays; television writers; tom stoppard; writing; Interviews